REPRESENTASI BERITA LINGKUNGAN HIDUP KASUS KABUT ASAP PADA HALAMAN UTAMA DI SURAT KABAR RIAU POS - DARA ADILA SANDY; SUYANTO " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
One of the causes of smog case in Riau is there’s no seriousness in anticipation of land and forest fires. Mass media is the most effective tool for increasing public awareness of the importance of environmental conservation, especially regarding the smog case. In this case, Riau Pos made smog as media agenda and consider this issue is very important through their preaching on main page. This study aims to determine the representation and social cognition of environmental news in smog case on the main page of Riau Pos newspaper. This study is a discourse analysis that uses qualitative methods with critical discourse analysis approach that pointed by Teun A van Dijk or better known as social cognition. The data collection techniques use observation, interviews, and documentation. Subject of this study is the smog case news on the main page of Riau Pos newspaper during June 2013. While the object is how representation of smog case news on the main page of Riau Pos newspaper. The results of this study, first, representation of environmental news smog case on the main page of Riau Pos newspaper raised the smog case based on the development of events. That found in thematic elements, schematic, semantic, syntactic, stylistic, and rhetorical. Second, social cognition environmental news on journalist are Riau Pos preach this case from various aspects ranging from the impact, causes, and efforts to mitigate them. This the need for information about smog surrounding the case can be met through the news. Social cognition of the readers are Riau Pos is still not up to preaching efforts to deter perpetrators of forest and land fires, and also news about the efforts that smog case is not repeated.Keyword : Representation, Smog Case, Environmental News